Endogenous Ethylene Concentration Is Not a Major Determinant of Fruit Abscission in Heat-Stressed Cotton (Gossypium hirsutum L.) - Najeeb, Ullah; Sarwar, Muhammad; Atwell, Brian J.; Bange, Michael P.; Tan, Daniel K. Y. (Frontiers in Plant Science, 2017)
We investigated the role of ethylene in the response of cotton to high temperature using cotton genotypes with genetically interrupted ethylene metabolism. In the first experiment, Sicot 71BRF and 5B (a lintless variant with compromised ethylene metabolism) were exposed to 45oC, either by instantaneous heat shock or by ramping temperatures by 3oC daily for one week. One day prior to the start of heat treatment, half the plants were sprayed with 0.8 mM of the ethylene synthesis inhibitor, aminoethoxyvinylglycine (AVG). In a subsequent experiment, Sicot 71BRF and a putatively heat-tolerant line, CIM 448, were exposed to 36oC or 45oC for one week, and half the plants were sprayed with 20 µM of the ethylene precursor, 1-aminocyclopropane-1-carboxlic acid, (ACC). High temperature exposure of plants in both experiments was performed at the peak reproductive phase (65-68 days after sowing). Elevated temperature (heat shock or ramping to 45oC) significantly reduced production and retention of fruits in all cotton lines used in this study. At the termination of heat treatment, cotton plants exposed to 45oC had at least 50% fewer fruits than plants under optimum temperature in all three genotypes, while plants at 36oC remained unaffected. Heat-stressed plants continued producing new squares (fruiting buds) after termination of heat stress but these squares did not turn into cotton bolls due to pollen infertility. In vitro inhibition of pollen germination by high temperatures supported this observation. Leaf photosynthesis (Pn) of heat-stressed plants (45oC) measured at the end of heat treatments remained significantly inhibited, despite an increased leaf stomatal conductance (gs), suggesting that high temperature impairs Pn independently of stomatal behaviour. Metabolic injury was supported by high relative cellular injury and low photosystem II yield of the heat-stressed plants, indicating that high temperature impaired photosynthetic electron transport. Both heat shock and ramping of heat significantly reduced ethylene release from cotton leaf tissues measured at the end of heat treatment but modulating ethylene production via AVG or ACC application had no significant effect on fruit production or retention in heat-stressed cotton plants. Instead, high temperature accelerated fruit abortion by impairing pollen development and / or restricting leaf photosynthesis.